Establishment of reference intervals of thyroid-related hormones for adults with normal liver function in Zhejiang Province by indirect method - Huang, Xiying; Yang, Xufeng (Frontiers in Endocrinology, 2024)
residents of coastal areas, focusing on extracting insights into the regional specificity of thyroid hormone levels. A thorough examination protocol was implemented, encompassing inquiries into thyroid health history, ultrasound screenings, palpations during thyroid surgery, detections of thyroid antibodies, and reviews of medication histories. Adherence to the CLSI C28-A3 guidelines(1-2) facilitated the derivation of RIs for thyroid-related hormones, subsequently juxtaposed against those provided by commercial entities.Results: The study delineated the following gender-and age-specific RIs for Thyroid-Stimulating Hormone (TSH): for males under 50 years, 0.57-3.37; males over 50 years, 0.51-4.03; females under 50 years, 0.53-3.91; and females over 50 years, 0.63-4.31. Further analysis revealed the RIs for Free Thyroxine (FT4), Free Triiodothyronine (FT3), Total Thyroxine (TT4), and Total Triiodothyronine (TT3) amongst males and females, with notable distinctions observed between the two genders and across age brackets. These findings are in stark contrast to the standardized intervals provided by manufacturers, particularly highlighting differences in TT3 and FT3 levels between genders and a tendency for TSH levels to increase with age.Conclusion: This research successfully establishes refined RIs for thyroid-related hormones within the Chinese coastal area populations, taking into account critical demographic factors such as gender and age. These tailored RIs are anticipated to significantly enhance the diagnostic accuracy for thyroid diseases, addressing the previously noted discrepancies with manufacturer-provided data and underscoring the importance of regionally and demographically adjusted reference intervals in clinical practice.